Otorrhea as a Sign of Medical Treatment Failure in Acute Otitis Media - Tzu-Chun Tsai; Pang-Mien Yu; Ren-Bin Tang; Hsin-Kai Wang; Ke-Chang Chang (Pediatrics and Neonatology)
We report two children with otitis media who developed facial palsy despite prompt antibiotic therapy. Brain images revealed silent mastoiditis. Persistent otorrhea may be a cautious sign of medical treatment failure or complication of acute otitis media, including mastoiditis or facial palsy. Delayed identification of coexisting mastoiditis or hesitation over surgical intervention may lead to treatment failure and complications. Adequate intravenous antibiotics and myringotomy provide reasonable and appropriate management to prevent permanent sequelae.